Synthesis of temporarily solubilised azo disperse dyes containing a β‐sulphatoethylsulphonyl group and dispersant‐free dyeing of polyethylene terephthalate fabric. (6th July 2016) - Kim, Jae Pil; Kim, Ji Su; Park, Jong Seung; Jang, Seung Soon; Lee, Jung Jin
Abstract : Disperse dyes containing a β‐sulphatoethylsulphonyl group have temporary solubility and can be applied for dispersant‐free dyeing of hydrophobic fibre. Six novel temporarily solubilised azo disperse dyes having a β‐sulphatoethylsulphonyl group in their structures were synthesised, and their dyeing properties on polyester were investigated. As a dye intermediate, a diazo component having dibromo groups was prepared, and 4‐diethylamino‐4′‐(2‐sulphatoethylsulphonyl‐4, 6‐dibromo)azobenzene dyes were prepared by a diazo‐coupling reaction. Then, the dyes containing dicyano groups were prepared by cyanation of corresponding dyes with dibromo groups. The absorption maxima of the dyes were affected by the substituents in the diazo and coupling component rings and varied from 434 to 616 nm in dimethylformamide. Polyethylene terephthalate woven fabric could be dyed with the synthesised temporarily solubilised dyes without using any dispersants. Dyebath pH affected the K / S value at maximum absorption as well as percentage exhaustion on polyethylene terephthalate fabric, and the optimum pH was 5. The dyes gave brownish orange, red, purple, and greenish blue hues on polyethylene terephthalate fabrics, and colour build‐up was good. Wash fastness was good to excellent, rubbing fastness was moderate to excellent, and light fastness was poor to moderate.